2019
DOI: 10.1111/1750-3841.14726
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Some Ingredients and Energy Content on Front‐of‐Pack Cereal Bar Labeling as Drivers of Choice and Perception of Healthiness: A Case Study with Exercisers

Abstract: The objective of this study was to explore the drivers of choice and perceptions of healthiness that specific ingredient or energy content information displayed on the front‐of‐pack label of cereal bars triggers among different groups of consumers. The participants (18 to 50 years old), classified as exercisers (n = 103, 52 women) or nonexercisers (n = 101, 51 women), completed a questionnaire and then rated their interest using images of cereal bars that varied in four characteristics (“With fruit,” “With cho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 41 publications
1
11
0
Order By: Relevance
“…Centurión, Machín, and Ares (2019) and Salazar et al. (2019) indicated that label information influenced consumers’ choice and healthfulness perception. BSG's “rich in fiber” message had a significant positive effect on purchase intent.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Centurión, Machín, and Ares (2019) and Salazar et al. (2019) indicated that label information influenced consumers’ choice and healthfulness perception. BSG's “rich in fiber” message had a significant positive effect on purchase intent.…”
Section: Resultsmentioning
confidence: 99%
“…While snacking behavior is often associated with an unhealthy diet and raises concerns about diet quality (Lambert, Mann, Partacz, & Jurss, 2020; Sogari et al., 2018), in the Western market, cereal bars are viewed as “healthy” alternatives to more traditional confections (Bower & Whitten, 2000). The versatility of the cereal bars ingredient formulations (Salazar et al., 2019) allows the ready adoption of an ingredient, such as BSG. The rate of successful introduction for new products in the market is related to product optimization, which includes meeting consumer expectations (Giacalone, 2018).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the nutritional quality of cereal bars varied greatly [35], and they are only slightly more natural than chocolate bars [62], which may be a reason to change the choice of bars in the future. In addition, for the consumer, a healthier fruit and cereal bar should still be a tasty bar, and at the same time, chocolate plays an important role in the consumer's liking of cereal bars [63,64] so eliminating it from the product by replacement with fruit may not always be acceptable. Further research on the consumer acceptability of cereal bars with regard to their composition and also motives of choice is needed.…”
Section: Discussionmentioning
confidence: 99%
“…• Fruit Mango (Mangifera indica L.) variety Tommy Atkins was selected because of its frequent consumption in the local diet and the strong production of these crops in the region where the plant is located. Additionally, this type of mango has shown results in transformation studies [13,14]. Slice maturation and thickness are the main factors that affect the drying results.…”
Section: Drying Parametersmentioning
confidence: 99%